1976
DOI: 10.1080/00365517609054495
|View full text |Cite
|
Sign up to set email alerts
|

The Estimated Daily Loss of Trace Elements from Normal Skin by Desquamation

Abstract: The content of 21 elements (As, Au, Br, Ca, Cd, Co, Cr, Cs, Cu, Fe, Hg, K, La, Mo, P, Rb, Sb, Sc, Se, W and Zn) in normal epidermis has been determined with the aid of neutron activation analysis. The dermal loss of these elements via desquamation has been calculated in view of its possible importance in balance studies. For the bulk elements Ca, K and P, the calculated daily loss is considered to be negligible. For some of the trace elements, however, the loss may be appreciable. The daily loss of Fe by desqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…Fig. 3 is an attempt to summarize the quantitative aspects of Zn metabolism in adult man on the basis of the presently available data (1, 9,23,25,30,33,36). Obviously, further research is necessary to clarify several details, particularly concerning sweat and urinary elimination of Zn in athletes.…”
Section: 116mentioning
confidence: 99%
“…Fig. 3 is an attempt to summarize the quantitative aspects of Zn metabolism in adult man on the basis of the presently available data (1, 9,23,25,30,33,36). Obviously, further research is necessary to clarify several details, particularly concerning sweat and urinary elimination of Zn in athletes.…”
Section: 116mentioning
confidence: 99%
“…Daily absorption of approximately 1mg of dietary iron through the gut is balanced by an equal amount excreted through the stool (0.6mg/d), urine (0.15–0.2mg/d) and skin (0.2–0.25mg/d)[8]. Desquamation of keratinocytes accounts for the 20–25% of absorbed iron that is lost through skin [9–11]; very little is lost through sweat [12, 13]. Total body iron content is normally regulated at the level of absorption from the gut: absorption is increased when body stores are low, limited when body stores are high.…”
Section: Introductionmentioning
confidence: 99%
“…Its selenium content was found to be within +5-io",, of the certified value. It would seem reasonable to compare our epidermal figure with that of Molin & Wester (1976), although we believe it is essential to make comparisons between identical skin sites.…”
Section: Discussionmentioning
confidence: 99%
“…Persigehl et al (1977) found that the concentration of selenium in skin decreased with age. In an investigation of daily losses of trace elements from normal skin by desquamation, Molin & Wester (1976) found the content of selenium in the epidermis to be 11+ 052 p.p.m. dry weight.…”
mentioning
confidence: 99%